Rancang Bangun Game Pengenalan Tari dan Alat Musik Suku Sasak - Widyaswari, Marshanda Raihan; Prawesty, Maharani Dian; Sabina, Adnisa; Gultom, Edelin; Zen, Bita (LPPM Universitas Dinamika Bangsa, 2024)
Utilizing technology, particularly through interactive multimedia learning, proves effective in enhancing the integration of cultural understanding and preservation in modern education. This medium serves not only as a crucial teaching tool but also facilitates students' comprehension of learning materials actively, enabling them to attain a deeper understanding. The aim of this research is to develop interactive multimedia to introduce the culture of the Sasak tribe, one of the over 300 ethnic groups in Indonesia. Employing the Multimedia Development Life Cycle (MDLC) approach, the study creates the educational application flow, starting from the initial display until users can explore educational content and participate in games. Through Alpha and Beta testing, the application achieves a high rating (4.64 out of 5) in terms of functionality, display, and user satisfaction. The publication is done through itch.io with the link https://dianmaharani17.itch.io/sasak-riddles-game. This application serves as an effective interactive learning tool about the dance and musical instruments of the Sasak tribe, enriching cultural diversity in Indonesia